Clinical performance of serum isoform [‐2]proPSA (p2PSA), and its derivatives %p2PSA and the Prostate Health Index, in men aged <60 years: results from a multicentric European study. (26th March 2015) - Fossati, Nicola; Lazzeri, Massimo; Haese, Alexander; McNicholas, Thomas; de la Taille, Alexandre; Buffi, Nicolò Maria; Lughezzani, Giovanni; Gadda, Giulio Maria; Lista, Giuliana; Larcher, Alessandro; Abrate, Alberto; Mistretta, Francesco; et al.
Abstract : Objectives: To test the hypothesis that [‐2]proPSA (p2PSA) and its derivatives are more accurate than total prostate‐specific antigen (tPSA), free prostate‐specific antigen (fPSA) and fPSA as percentage of tPSA (%fPSA) in detecting prostate cancer (PCa) in men aged <60 years. Patients and Methods: The analysis consisted of a nested case–control study from the PRO‐ PSA Multicentric European Study (PROMEtheuS) project. The primary outcomes were measures of sensibility, specificity and accuracy of serum p2PSA, p2PSA as percentage of fPSA (%p2PSA) and Beckman Coulter prostate health index (PHI) in men aged <60 years who had undergone a prostate biopsy. The potential reduction in the number of unnecessary biopsies and the characteristics of the potentially missed PCa cases were reported as secondary outcomes. Multivariate logistic regression models were complemented by predictive accuracy and decision‐curve analyses. Results: Of the 1036 patients enrolled in the PROMEtheus project, 238 (22.9%) were aged < 60 years. PCa was found in 67 subjects (28.1%); p2PSA, %p2PSA and PHI values were significantly higher ( P < 0.001) among these subjects, while no differences were found in tPSA, fPSA and %fPSA values. On univariate analysis, %p2PSA (area under the curve [AUC]: 0.704) and PHI (AUC: 0.7) were the most accurate predictors, and these significantly outperformed tPSA (AUC: 0.549), fPSA (AUC: 0.511) and %fPSA (AUC: 0.557) in the prediction of PCa at biopsy ( P ≤ 0.001). In multivariate logistic regression models, %p2PSA and PHI achieved independent predictor status and significantly increased the accuracy of multivariate models by 6.3 and 7.6%, respectively ( P ≤ 0.05). Conclusion: PHI and %p2PSA are more accurate than the reference standard tests in predicting PCa in young men.